Institutional convergence for agricultural development: The changing role of extension - Ananth, Pavanasam Natarajan; Babu, Suresh Chandra; Barik, Nagesh Kumar; Dash, Ajaya Kumar; Sundaray, J. K. (Agricultural Extension in South Asia, 2019)
Extension agencies globally face the twin challenges of limited finances and manpower. However, some extension agencies manage these challenges and achieve larger impacts by converging their efforts with others. Based on their experiences with convergence of activities at the Krishi Vigyan Kendra (KVK) in Khordha under ICAR-Central Institute for Freshwater Aquaculture, Bhubaneswar, Odisha, PN Ananth, S Babu, NK Barik, AK Dash and JK Sundaray demonstrates how convergence at the KVK level can enhance innovation and impact.